2018
DOI: 10.2196/mhealth.8123
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile Phone Ownership Is Not a Serious Barrier to Participation in Studies: Descriptive Study

Abstract: BackgroundRather than providing participants with study-specific data collection devices, their personal mobile phones are increasingly being used as a means for collecting geolocation and ecological momentary assessment (EMA) data in public health research.ObjectiveThe purpose of this study was to (1) describe the sociodemographic characteristics of respondents to an online survey screener assessing eligibility to participate in a mixed methods study collecting geolocation and EMA data via the participants’ p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…First, the study utilized an online screener for initial participant recruitment and the protocol required participants to have an iPhone or Android smartphone, which may have been a barrier to enrollment for individuals lacking Internet access and/or the requirement cellphone, respectively. However, approximately 72% individuals who were screened met all smartphone inclusion criteria, suggesting that smartphone ownership was not a major barrier to study participation for individuals with Internet access (Harvey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, the study utilized an online screener for initial participant recruitment and the protocol required participants to have an iPhone or Android smartphone, which may have been a barrier to enrollment for individuals lacking Internet access and/or the requirement cellphone, respectively. However, approximately 72% individuals who were screened met all smartphone inclusion criteria, suggesting that smartphone ownership was not a major barrier to study participation for individuals with Internet access (Harvey et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that youths from low socioeconomic status (SES) backgrounds are more likely to own a mobile phone (e.g., Byun et al, 2013), to access their phones more frequently (Lenhart, 2015), and in general to spend more time on their phones (Thomas et al, 2010) relative to those from higher SES contexts. This intersection of increased stress exposure and technological access (e.g., Harvey et al, 2018) makes the possible benefits of online coping especially compelling.…”
Section: Psychological Science Empirical Articlementioning
confidence: 99%
“…The authors found that none of the demographics they used to screen patients were significantly associated with smartphone ownership. However, participants were recruited by an online screener, which could itself exclude individuals who do not own a smartphone [11]. Studies that include participants based on their disease status and assess smartphone ownership are needed to determine which patients could be excluded from mHealth interventions if they are required to use their own smartphone.…”
Section: Introductionmentioning
confidence: 99%